Male caffeine and alcohol intake in relation to semen parameters and in vitro fertilization outcomes among fertility patients. (10th February 2017) - Karmon, A. E.; Toth, T. L.; Chiu, Y.‐H.; Gaskins, A. J.; Tanrikut, C.; Wright, D. L.; Hauser, R.; Chavarro, J. E.; ,
Summary: Much of the literature on the impact of male caffeine and alcohol intake on reproductive outcomes has utilized semen quality as a proxy for male fertility, although semen parameters have a limited predictive value for spontaneous pregnancy. The objective of this study was to investigate whether male caffeine and alcohol intakes are associated with semen parameters and assisted reproductive technology outcome. The Environment and Reproductive Health Study, an ongoing prospective cohort study, enrolls subfertile couples presenting for treatment at an academic fertility center (2007–2012). A total of 171 men with 338 semen analyses and 205 assisted reproductive technology cycles were included in this analysis. Diet was assessed using a 131‐item food frequency questionnaire. Mixed models adjusting for potential confounders were used to evaluate the relationships of male caffeine and alcohol intakes with semen parameters and assisted reproductive technology outcomes. There was no association between male caffeine and alcohol intake and semen quality. Male caffeine intake was negatively related to live birth after assisted reproductive technologies ( p ‐trend < 0.01), and male alcohol intake was positively related to live birth after assisted reproductive technologies ( p ‐trend = 0.04). Adjusted live birth rate among couples with a male partner in the highest quartile of caffeine intake (≥272 mg/day) compared to couples with a male partner in the lowest quartile of intake (<99 mg/day) was 19% vs. 55%, respectively, p  < 0.01. In terms of alcohol intake, adjusted live birth rate among couples with a male partner in the highest quartile of alcohol intake (≥22 g/day) compared to couples with a male partner in the lowest quartile of intake (<3 g/day) was 61% vs. 28%, respectively, p  = 0.05. In conclusion, male pre‐treatment caffeine and alcohol intakes were associated with live birth after assisted reproductive technologies, but not with semen parameters, among fertility patients.